The forecasting power of consumer attitudes for consumer spending - Michelle L. Barnes; Giovanni P. Olivei (Federal Reserve Bank of Boston, 2014)
We assess the ability of the Reuters/Michigan Surveys of Consumers to predict future changes in consumer expenditures. The information in the Surveys is summarized by means of principal components of consumer attitudes with respect to income and wealth, interest rates, and prices. These summary measures contain information that goes beyond the information captured by the Index of Consumer Sentiment from the same Surveys. The summary measures have forecasting power for aggregate consumption behavior, even when controlling for current and future economic fundamentals. These measures also help to explain a nontrivial portion of consumption and other real activity forecast errors from the Survey of Professional Forecasters and the Federal Reserve Board's Greenbook. This finding is consistent with the ability of these summary measures to predict consumption even when conditioning on a broader set of fundamentals and on forecasters' judgmental assessments of developments that are not easily quantifiable.
Keywords: E21; E27; E52; E66; 330